Experimental Study on Compressive Strength of Belian Wood Strengthened with Concrete Jacketing - Manurung, Sondang Sylvia; Violeta, Iona (Jurnal Teknik Sipil, 2022)
Belian wood is very well known building construction material and been used since long time ago for both structural and non-structural elements. Somehow belian wood buildings which have been being exist for many years or some functional changes in use need structural strengthening. One of the most popular strengthening method is concrete jacketing as it is practical and mechanically increase the capacity of existing structures. This research is conducted in order to experimentally study on the capacity increase of the belian wood strengthened with the concrete jacketing and the effectiveness of shear connector used.This research used 15cmx30cm cylinder samples with 8cmx8cm belian wood as the core. There were five variations of shear connectors used. First variation (S1) without shear connector, second variation (S2) with sieve wiring coil, third variation (S3) with 6mm of diameter reinforcement coil, fourth variation (S4) with safety wiring coil, and fifth variation (S5) with 2 inches of diameter nails. There were 10 samples for each variation. All samples were tested and compared to the compressive strength of conventional belian wood without strengthening. It results in third variation with 6mm of diameter reinforcement coil (S3) come out with the highest compressive strength among all with 75.909% of increase whereas the first variation without shear connector (S1) resulting in highest increase of compressive strength after the concrete collapse with 25.493% of increase which showed the importance of shear connector between those different materials.